Increasing grassland productivity and reducing environmental N losses – Multiple benefits of advanced cattle slurry separation - Jincheng Han; Rainer Gasche; Benjamin Wolf; Steffen Schweizer; Noelia Garcia-Franco; Martin Wiesmeier; Ralf Kiese; Ulrike Ostler; Diana Andrade; Michael Schloter; Marcus Schlingmann; Heinz Rennenberg; et al. (Agriculture, Ecosystems & Environment, 2026)

Flux Footprints: A Critical Link to Bridge Eddy‐Covariance Measurements With Models, Remote Sensing, and Other Observations - Housen Chu; Stefan Metzger; Zutao Ouyang; Anne Griebel; Koong Yi; David Durden; Sebastian Wolf; Kuno Kasak; Camilo Rey‐Sanchez; Leila Constanza Hernandez Rodriguez; Patty Oikawa; Nicola Falco; et al. (Global Change Biology, 2026)
Global networks of eddy‐covariance flux towers play a pivotal role in enhancing our predictive understanding of carbon and water cycling of biological systems in response to regional and global environmental change. Despite their broad application in numerous studies, the spatial aspects of the flux measurements have often been ignored or treated ambiguously, thereby remaining a primary source of uncertainty. The area contributing to the flux—referred to as the flux footprint—varies over time depending on wind direction, atmospheric turbulence, effective measurement heights, surface characteristics, and mesoscale forcings. The footprint dynamics, along with underlying source‐sink heterogeneity, lead to spatial and temporal variability in the sensed fluxes, complicating the interpretation of flux data and their integration with a range of observations and models. This article addresses this critical link by reviewing the most up‐to‐date research, identifying knowledge gaps and challenges, and pointing out future research needs and opportunities. We begin with an overview of the current state of footprint modeling and its applications, from single‐site studies to large‐scale syntheses, summarizing how flux footprints have been used to interpret spatial flux variability and to integrate flux data with models, remote sensing, and other observations. We highlight how this critical spatial aspect could complicate the processing of eddy‐covariance fluxes, the definition of mass and energy continuity, and the interpretation of flux response functions and parameters, all of which have significant implications for numerous applications and research. We then point out potential opportunities and future research needs to bridge this knowledge gap, highlighting both readily available and prominent emerging ones. We conclude by urging the scientific community to (re)consider the spatiotemporal dynamics of eddy‐covariance flux measurements, and to investigate and evaluate potential approaches across scales, applications, and disciplines.

FracFeed : Global database of the fraction of feeding predators - Mark Novak; Paige Foust; Shannon Hennessey; Brian P. Tanis; Kyle E. Coblentz; Christopher Wolf; Leah M. Segui; Jeremy S. Henderson; Kurt E. Ingeman; Landon P. Falke; Tamara J. Layden; Daniel J. Gradison; et al. (Ecology, 2026)
The proportion of individuals that are found to have empty stomachs during a survey of a predator population's diet has been used as an indicator of the average individual's state of energy balance and of the degree to which its feeding rate (i.e., its functional response) is saturated with respect to prey availability. As such, the proportion of empty stomachs provides insights into the effects of prey on predators and vice versa, although it is typically unreported in deference to descriptions of the contents of the non‐empty stomachs. The FracFeed database is an ongoing compilation of the proportions of empty and non‐empty stomachs (for gut content surveys) and of feeding and not feeding individuals (for direct observation surveys) reported in publications of predator diet surveys. FracFeed contains data from 4920 diet surveys on 1507 taxa (>4.3 million individuals) spanning cnidarians, ctenophores, chaetognaths, birds, annelids, amphibians, arthropods, mammals, mollusks, reptiles, echinoderms, and fishes that were surveyed in terrestrial, marine, and freshwater ecosystems across the globe over more than 135 years (1887–2023). For most surveys, covariate data include information on the spatial and temporal extent of the diet survey, its central geographical coordinates, the method by which the survey was performed (lethal gut contents, lavage, or direct observation), as well as each predator's standardized taxonomic name and identifier in the Open Tree of Life, its body mass (compiled mostly from independent compilations and additional publications), and its apparent diet's taxonomic richness and resolution. We appeal to more researchers who perform diet surveys to report on the number of empty stomachs they find and encourage additional contributions to the database—particularly from underrepresented geographic regions (e.g., North and Central Asia, North and Central Africa)—to help grow its scope and utility. The database is provided under a CC‐BY‐NC‐S4 4.0 license. Users are requested to cite this data paper when using the data.

Impact of neighbor-level disadvantage on survival outcomes in head and neck squamous cell carcinoma - William J. Benjamin; Siddhi Patil; Elham Mohebbi; Sophia Latif; Chamila Perera; Emily Bellile; Kai Wang; Maureen A. Sartor; Jeremy M. G. Taylor; Gregory T. Wolf; Steven B. Chinn; Laura S. Rozek (Cancer Causes & Control, 2025)

Effect of slurry bio-acidification and leonardite addition on ammonia and greenhouse gas emissions in soil-plant mesocosms - Fawad Khan; Samuel Franco-Luesma; Baldur Janz; Michael Dannenmann; Rainer Gasche; Andreas Gattinger; Waqas Qasim; Ralf Kiese; Benjamin Wolf (Journal of Cleaner Production, 2025)

Lysimeter-based full fertilizer 15N balances corroborate direct dinitrogen emission measurements using the 15N gas flow method - Irina Yankelzon; Lexie Schilling; Klaus Butterbach-Bahl; Rainer Gasche; Jincheng Han; Lorenz Hartl; Julia Kepp; Amanda Matson; Ulrike Ostler; Clemens Scheer; Katrin Schneider; Arne Tenspolde; et al. (Biology and Fertility of Soils, 2025)
The 15 N gas flux ( 15 NGF) method allows for direct in situ quantification of dinitrogen (N 2 ) emissions from soils, but a successful cross-comparison with another method is missing. The objectives of this study were to quantify N 2 emissions of a wheat rotation using the 15 NGF method, to compare these N 2 emissions with those obtained from a lysimeter-based 15 N fertilizer mass balance approach, and to contextualize N 2 emissions with 15 N enrichment of N 2 in soil air. For four sampling periods, fertilizer-derived N 2 losses ( 15 NGF method) were similar to unaccounted fertilizer N fates as obtained from the 15 N mass balance approach. Total N 2 emissions ( 15 NGF method) amounted to 21 ± 3 kg N ha − 1 , with 13 ± 2 kg N ha − 1 (7.5% of applied fertilizer N) originating from fertilizer. In comparison, the 15 N mass balance approach overall indicated fertilizer-derived N 2 emissions of 11%, equivalent to 18 ± 13 kg N ha − 1 . Nitrous oxide (N 2 O) emissions were small (0.15 ± 0.01 kg N ha − 1 or 0.1% of fertilizer N), resulting in a large mean N 2 :(N 2 O + N 2 ) ratio of 0.94 ± 0.06. Due to the applied drip fertigation, ammonia emissions accounted for < 1% of fertilizer-N, while N leaching was negligible. The temporal variability of N 2 emissions was well explained by the δ 15 N 2 in soil air down to 50 cm depth. We conclude the 15 NGF method provides realistic estimates of field N 2 emissions and should be more widely used to better understand soil N 2 losses. Moreover, combining soil air δ 15 N 2 measurements with diffusion modeling might be an alternative approach for constraining soil N 2 emissions.

Integrated rather than organic farming history facilitates soil nitrogen turnover and N2O reduction in a green rye – silage maize cropping sequence - Fawad Khan; Samuel Franco-Luesma; Michael Ulrich Dannenmann; Rainer Gasche; Andreas Gattinger; Frederik Hartmann; Beatrice Tobisch; Ralf Kiese; Benjamin Wolf (Biology and Fertility of Soils, 2025)
Soil gross mineral N production and consumption processes are crucial regulators of plant productivity and N loss from croplands. Substituting synthetic fertilizers by integrating legumes in cultivation systems is common in organic farming, but research on its long-term impact on dynamics of gross soil N transformation and associated environmental N loss is scarce. In particular, studies at a temporal resolution that allows for a mechanistic understanding of long-term effects of organic farming are missing. Therefore, we determined gross N turnover rates of ammonification, nitrification, and ammonium and nitrate immobilization at monthly temporal resolution during a full green rye-maize cropping sequence. Measurements were carried out at sites with same pedo-climatic background but organic farming (OF) and integrated farming (IF) history. During green rye growing, N turnover rates for OF and IF were low and not significantly different, likely owing to low temperatures. During silage maize growing, IF exhibited significantly higher average N turnover rates of 1.86, 4.46, and 5.57 mg N kg⁻ 1 dry soil d⁻ 1 for gross ammonification, ammonium immobilization, and nitrate immobilization, respectively, compared to OF values of 1.11, 1.80, and 2.90 mg N kg⁻ 1 dry soil d⁻ 1 . The significantly higher N turnover rates were likely due to higher soil organic C, N and microbial biomass which result from different long-term management practices. Especially the increased immobilization potential on the IF site contributed to significantly lower area-scaled N₂O emissions (1.45 vs. 4.36 kg N ha⁻ 1 ) during periods of high nitrification. This shows that for low SOC soils, integrated farming history with high C return enhances soil N cycling and reduces the risk of N losses in the form of N 2 O emission.

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Spatial-temporal patterns of foliar and bulk soil 15N isotopic signatures across a heterogeneous landscape: Linkages to soil N status, nitrate leaching, and N2O fluxes - Elizabeth Gachibu Wangari; Ricky Mwangada Mwanake; Tobias Houska; David Kraus; Hanna-Marie Kikowatz; Benjamin Wolf; Gretchen M. Gettel; Lutz Breuer; Per Ambus; Ralf Kiese; Klaus Butterbach-Bahl (Soil Biology and Biochemistry, 2024)

An innovative soil mesocosm system for studying the effect of soil moisture and background NO on soil surface C and N trace gas fluxes - Logapragasan Subramaniam; Florian Engelsberger; Benjamin Wolf; Nicolas Brüggemann; Laurent Philippot; Michael Dannenmann; Klaus Butterbach-Bahl (Biology and Fertility of Soils, 2024)
Nitric oxide (NO) is a key substance in atmospheric chemistry, influencing the formation and destruction of tropospheric ozone and the atmosphere's oxidizing capacity. It also affects the physiological functions of organisms. NO is produced, consumed, and emitted by soils, the effects of soil NO concentrations on microbial C and N cycling and associated trace gas fluxes remain largely unclear. This study describes a new automated 12-chamber soil mesocosm system that dynamically changes incoming airflow composition. It was used to investigate how varying NO concentrations affect soil microbial C and N cycling and associated trace gas fluxes under different moisture conditions (30% and 50% WFPS). Based on detection limits for NO, NO 2 , N 2 O, and CH 4 fluxes of < 0.5 µg N or C m −2 h −1 and for CO 2 fluxes of < 1.2 mg C m −2 h −1 , we found that soil CO 2 , CH 4 , NO, NO 2 , and N 2 O were significantly affected by different soil moisture levels. After 17 days cumulative fluxes at 50% WFPS increased by 40, 400, and 500% for CO 2 , N 2 O, and CH 4 , respectively, when compared to 30% WFPS. However, cumulative fluxes for NO, and NO 2 , decreased by 70, and 40%, respectively, at 50% WFPS when compared to 30% WFPS. Different NO concentrations tended to decrease soil C and N fluxes by about 10–20%. However, with the observed variability among individual soil mesocosms and minor fluxes change. In conclusion, the developed system effectively investigates how and to what extent soil NO concentrations affect soil processes and potential plant–microbe interactions in the rhizosphere.

Reducing N fertilization in the framework of the European Farm to Fork strategy under global change: Impacts on yields, N2O emissions and N leaching of temperate grasslands in the Alpine region - Márcio dos Reis Martins; Christof Ammann; Carolin Boos; Pierluigi Calanca; Ralf Kiese; Benjamin Wolf; Sonja G. Keel (Agricultural Systems, 2024)

Regulating soil microclimate and greenhouse gas emissions with rye mulch in cabbage cultivation - Bryan A. Dix; Michael E. Hauschild; Wiebke Niether; Benjamin Wolf; Andreas Gattinger (Agriculture, Ecosystems & Environment, 2024)

SNAPSHOT USA 2021: A third coordinated national camera trap survey of the U nited S tates - Hila Shamon; Roi Maor; Michael V. Cove; Roland Kays; Jessie Adley; Peter D. Alexander; David N. Allen; Maximilian L. Allen; Cara L. Appel; Evan Barr; Erika L. Barthelmess; Carolina Baruzzi; et al. (Ecology, 2024)
SNAPSHOT USA is a multicontributor, long‐term camera trap survey designed to survey mammals across the United States. Participants are recruited through community networks and directly through a website application ( https://www.snapshot-usa.org/ ). The growing Snapshot dataset is useful, for example, for tracking wildlife population responses to land use, land cover, and climate changes across spatial and temporal scales. Here we present the SNAPSHOT USA 2021 dataset, the third national camera trap survey across the US. Data were collected across 109 camera trap arrays and included 1711 camera sites. The total effort equaled 71,519 camera trap nights and resulted in 172,507 sequences of animal observations. Sampling effort varied among camera trap arrays, with a minimum of 126 camera trap nights, a maximum of 3355 nights, a median 546 nights, and a mean 656 ± 431 nights. This third dataset comprises 51 camera trap arrays that were surveyed during 2019, 2020, and 2021, along with 71 camera trap arrays that were surveyed in 2020 and 2021. All raw data and accompanying metadata are stored on Wildlife Insights ( https://www.wildlifeinsights.org/ ), and are publicly available upon acceptance of the data papers. SNAPSHOT USA aims to sample multiple ecoregions in the United States with adequate representation of each ecoregion according to its relative size. Currently, the relative density of camera trap arrays varies by an order of magnitude for the various ecoregions (0.22–5.9 arrays per 100,000 km 2 ), emphasizing the need to increase sampling effort by further recruiting and retaining contributors. There are no copyright restrictions on these data. We request that authors cite this paper when using these data, or a subset of these data, for publication. Any use of trade, firm, or product names is for descriptive purposes only and does not imply endorsement by the US Government.

Delayed leaf greening involves a major shift in the expression of cytosolic and mitochondrial ribosomes to plastid ribosomes in the highly phosphorus-use-efficient Hakea prostrata (Proteaceae) - Toby Bird; Benjamin J. Nestor; Philipp E. Bayer; Guannan Wang; Albina Ilyasova; Clément E. Gille; Bryce E. H. Soraru; Kosala Ranathunge; Anita A. Severn-Ellis; Ricarda Jost; Wolf-Rüdiger Scheible; Maheshi Dassanayake; et al. (Plant and Soil, 2024)
Background and aims Hakea prostrata (Proteaceae) is a highly phosphorus-use-efficient plant native to southwest Australia. It maintains a high photosynthetic rate at low leaf phosphorus (P) and exhibits delayed leaf greening, a convergent adaptation that increases nutrient-use efficiency. This study aimed to provide broad physiological and gene expression profiles across leaf development, uncovering pathways leading from young leaves as nutrient sinks to mature leaves as low-nutrient, energy-transducing sources. Methods To explore gene expression underlying delayed greening, we analysed a de novo transcriptome for H. prostrata across five stages of leaf development. Photosynthesis and respiration rates, and foliar pigment, P and nitrogen (N) concentrations were determined, including the division of P into five biochemical fractions. Key results Transcripts encoding functions associated with leaf structure generally decreased in abundance across leaf development, concomitant with decreases in foliar concentrations of 85% for anthocyanins, 90% for P and 70% for N. The expression of genes associated with photosynthetic function increased during or after leaf expansion, in parallel with increases in photosynthetic pigments and activity, much later in leaf development than in species that do not have delayed greening. As leaves developed, transcript abundance for cytosolic and mitochondrial ribosomal proteins generally declined, whilst transcripts for chloroplast ribosomal proteins increased. Conclusions There was a much longer temporal separation of leaf cell growth from chloroplast development in H. prostrata than is found in species that lack delayed greening. Transcriptome-guided analysis of leaf development in H. prostrata provided insight into delayed greening as a nutrient-saving strategy in severely phosphorus-impoverished landscapes.

Demystifying the agronomic and environmental N performance of grain legumes across contrasting soil textures of central Germany - Ferdinando Binacchi; Wiebke Niether; Christopher Brock; Lucas Knebl; Andreas Brændholt; Benjamin Wolf; Andreas Gattinger (Agriculture, Ecosystems & Environment, 2023)

Characteristics of annual NH3 emissions from a conventional vegetable field under various nitrogen management strategies - Yan Wang; Zhisheng Yao; Yanqiang Wang; Guangxuan Yan; Baldur Janz; Xiaogang Wang; Yang Zhan; Rui Wang; Xunhua Zheng; Minghua Zhou; Bo Zhu; Ralf Kiese; et al. (Journal of Environmental Management, 2023)

Prevalence of higher-grade dysplasia in persistently high-risk human papillomavirus positive, cytology negative women after introduction of the new cervical cancer screening in Germany - Laura Berger; Maja Wolf-Breitinger; Christel Weiß; Benjamin Tuschy; Sebastian Berlit; Marc Sütterlin; Saskia Spaich (Cancer Causes & Control, 2023)
Purpose According to the recently implemented organized cervical cancer screening program in Germany, women older than 35 years with negative cytology but persistent high-risk human papilloma virus (hrHPV) infection > 12 months should be referred to colposcopy for further evaluation. This study aimed to present and dissect colposcopic and histopathological findings with particular focus on associated hrHPV genotypes. Methods This study is a retrospective analysis of clinical data from 89 hrHPV positive patients with normal cytology who underwent colposcopic examination at a certified dysplasia outpatient clinic in Germany in 2021. Results While 38 (43%) women had a normal colposcopic finding, 45 (51%) had minor and 6 (7%) major changes. Thirty-one (35%) of the women were HPV 16 and/or HPV 18 positive and 58 (65%) women were positive for other hrHPV only. Among patients who underwent colposcopy with biopsies (in case of an abnormal finding or type 3 transformation zone, n = 68), eight (12%) had cervical intraepithelial neoplasia (CIN) 3 and six (9%) had CIN 2. The proportion of women diagnosed with CIN 3 varied among different hrHPV genotypes (HPV 16: 11%, HPV 18: 33%, HPV 31: 27%, HPV 33: 33%, HPV 52: 33%). Conclusion Persistently hrHPV positive women with negative cytology are at increased risk of being diagnosed with CIN 3. As CIN 3 prevalence seems to differ with regard to hrHPV strain, immediate HPV genotyping for risk stratification and subsequent early referral for colposcopy might constitute a feasible strategy.

Impacts of slurry acidification and injection on fertilizer nitrogen fates in grassland - Mirella Schreiber; Elpida Bazaios; Barbara Ströbel; Benjamin Wolf; Ulrike Ostler; Rainer Gasche; Marcus Schlingmann; Ralf Kiese; Michael Dannenmann (Nutrient Cycling in Agroecosystems, 2023)
Low nitrogen (N) use efficiency of broadcast slurry application leads to nutrient losses, air and water pollution, greenhouse gas emissions and—in particular in a warming climate—to soil N mining. Here we test the alternative slurry acidification and injection techniques for their mitigation potential compared to broadcast spreading in montane grassland. We determined (1) the fate of 15 N labelled slurry in the plant-soil-microbe system and soil-atmosphere exchange of greenhouse gases over one fertilization/harvest cycle and (2) assessed the longer-term contribution of fertilizer 15 N to soil organic N formation by the end of the growing season. The isotope tracing approach was combined with a space for time climate change experiment. Simulated climate change increased productivity, ecosystem respiration, and net methane uptake irrespective of management, but the generally low N 2 O fluxes remained unchanged. Compared to the broadcast spreading, slurry acidification showed lowest N losses, thus increased productivity and fertilizer N use efficiency (38% 15 N recovery in plant aboveground plant biomass). In contrast, slurry injection showed highest total fertilizer N losses, but increased fertilization-induced soil organic N formation by 9–12 kg N ha −1 season −1 . Slurry management effects on N 2 O and CH 4 fluxes remained negligible. In sum, our study shows that the tested alternative slurry application techniques can increase N use efficiency and/or promote soil organic N formation from applied fertilizer to a remarkable extent. However, this is still not sufficient to prevent soil N mining mostly resulting from large plant N exports that even exceed total fertilizer N inputs.

Enteric methane emission estimates for Kenyan cattle in a nighttime enclosure using a backward Lagrangian Stochastic dispersion technique - Kevin Wolz; Sonja Leitner; Lutz Merbold; Benjamin Wolf; Matthias Mauder (Theoretical and Applied Climatology, 2022)
This study provides methane (CH4) emission estimates for mature female African beef cattle in a semi-arid region in Southern Kenya using open-path laser spectroscopy together with a backward Lagrangian Stochastic (bLS) dispersion modeling technique. We deployed two open-path lasers to determine 10-min averages of line-integrated CH 4 measurements upwind and downwind of fenced enclosures (so-called bomas: a location where the cattle are gathered at night) during 14 nights in September/October 2019. The measurements were filtered for wind direction deviations and friction velocity before the model was applied. We compared the obtained emission factors (EFs) with the Intergovernmental Panel on Climate Change (IPCC) Tier 1 estimates for the Sub-Saharan African (SSA) countries, which were mostly derived from studies carried out in developed countries and adapted to the conditions in Africa. The resulting EF of 75.4 ± 15.99 kg year −1 and the EFs calculated from other studies carried out in Africa indicate the need for the further development of region-specific EFs depending on animal breed, livestock systems, feed quantity, and composition to improve the IPCC Tier 1 estimates.

Intensive slurry management and climate change promote nitrogen mining from organic matter-rich montane grassland soils - Marcus Schlingmann; Ursina Tobler; Bernd Berauer; Noelia Garcia-Franco; Peter Wilfahrt; Martin Wiesmeier; Anke Jentsch; Benjamin Wolf; Ralf Kiese; Michael Dannenmann (Plant and Soil, 2020)
Aims Consequences of climate change and land use intensification on the nitrogen (N) cycle of organic-matter rich grassland soils in the alpine region remain poorly understood. We aimed to identify fates of fertilizer N and to determine the overall N balance of an organic-matter rich grassland in the European alpine region as influenced by intensified management and warming. Methods We combined 15 N cattle slurry labelling with a space for time climate change experiment, which was based on translocation of intact plant-soil mesocosms down an elevational gradient to induce warming of +1 °C and + 3 °C. Mesocosms were subject to either extensive or intensive management. The fate of slurry-N was traced in the plant-soil system. Results Grassland productivity was very high (8.2 t - 19.4 t dm ha −1 yr −1 ), recovery of slurry 15 N in mowed plant biomass was, however, low (9.6–14.7%), illustrating low fertilizer N use efficiency and high supply of plant available N via mineralization of soil organic matter (SOM). Higher 15 N recovery rates (20.2–31.8%) were found in the soil N pool, dominated by recovery in unextractable N. Total 15 N recovery was approximately half of the applied tracer, indicating substantial loss to the environment. Overall, high N export by harvest (107–360 kg N ha −1 yr −1 ) markedly exceeded N inputs, leading to a negative grassland N balance. Conclusions Here provided results suggests a risk of soil N mining in montane grasslands, which increases both under climate change and land use intensification.

Dinitrogen (N2) pulse emissions during freeze-thaw cycles from montane grassland soil - Xing Wu; Zhe Chen; Ralf Kiese; Jin Fu; Silvia Gschwendter; Michael Schloter; Chunyan Liu; Klaus Butterbach-Bahl; Benjamin Wolf; Michael Dannenmann (Biology and Fertility of Soils, 2020)
Short-lived pulses of soil nitrous oxide (N 2 O) emissions during freeze-thaw periods can dominate annual cumulative N 2 O fluxes from temperate managed and natural soils. However, the effects of freeze thaw cycles (FTCs) on dinitrogen (N 2 ) emissions, i.e., the dominant terminal product of the denitrification process, and ratios of N 2 /N 2 O emissions have remained largely unknown because methodological difficulties were so far hampering detailed studies. Here, we quantified both N 2 and N 2 O emissions of montane grassland soils exposed to three subsequent FTCs under two different soil moisture levels (40 and 80% WFPS) and under manure addition at 80% WFPS. In addition, we also quantified abundance and expression of functional genes involved in nitrification and denitrification to better understand microbial drivers of gaseous N losses. Our study shows that each freeze thaw cycle was associated with pulse emissions of both N 2 O and N 2 , with soil N 2 emissions exceeding N 2 O emissions by a factor of 5–30. Increasing soil moisture from 40 to 80% WFPS and addition of cow slurry increased the cumulative FTC N 2 emissions by 102% and 77%, respectively. For N 2 O, increasing soil moisture from 40 to 80% WFPS and addition of slurry increased the cumulative emissions by 147% and 42%, respectively. Denitrification gene cnorB and nosZ clade I transcript levels showed high explanatory power for N 2 O and N 2 emissions, thereby reflecting both N gas flux dynamics due to FTC and effects of different water availability and fertilizer addition. In agreement with several other studies for various ecosystems, we show here for mountainous grassland soils that pulse emissions of N 2 O were observed during freeze-thaw. More importantly, this study shows that the freeze-thaw N 2 pulse emissions strongly exceeded those of N 2 O in magnitude, which indicates that N 2 emissions during FTCs could represent an important N loss pathway within the grassland N mass balances. However, their actual significance needs to be assessed under field conditions using intact plant-soil systems.

Simultaneous quantification of N 2 , NH 3 and N 2 O emissions from a flooded paddy field under different N fertilization regimes - Longlong Xia; Xiaobo Li; Qianqian Ma; Shu Kee Lam; Benjamin Wolf; Ralf Kiese; Klaus Butterbach‐Bahl; Deli Chen; Zhian Li; Xiaoyuan Yan (Global Change Biology, 2020)
Gaseous nitrogen (N) emissions, especially emissions of dinitrogen (N 2 ) and ammonia (NH 3 ), have long been considered as the major pathways of N loss from flooded rice paddies. However, no studies have simultaneously evaluated the overall response of gaseous N losses to improved N fertilization practices due to the difficulties to directly measure N 2 emissions from paddy soils. We simultaneously quantified emissions of N 2 (using membrane inlet mass spectrometry), NH 3 and nitrous oxide (N 2 O) from a flooded paddy field in southern China over an entire rice‐growing season. Our field experiment included three treatments: a control treatment (no N addition) and two N fertilizer (220 kg N/ha) application methods, the traditional surface application of N fertilizer and the incorporation of N fertilizer into the soil. Our results show that over the rice‐growing season, the cumulative gaseous N losses from the surface application treatment accounted for 13.5% (N 2 ), 19.1% (NH 3 ), 0.2% (N 2 O) and 32.8% (total gaseous N loss) of the applied N fertilizer. Compared with the surface application treatment, the incorporation of N fertilizer into the soil decreased the emissions of NH 3 , N 2 and N 2 O by 14.2%, 13.3% and 42.5%, respectively. Overall, the incorporation of N fertilizer into the soil significantly reduced the total gaseous N loss by 13.8%, improved the fertilizer N use efficiency by 14.4%, increased the rice yield by 13.9% and reduced the gaseous N loss intensity (gaseous N loss/rice yield) by 24.3%. Our results indicate that the incorporation of N fertilizer into the soil is an effective agricultural management practice in ensuring food security and environmental sustainability in flooded paddy ecosystems.

Far-red light acclimation in diverse oxygenic photosynthetic organisms - Benjamin M. Wolf; Robert E. Blankenship (Photosynthesis Research, 2019)

Coring of Antarctic Subglacial Sediments - Da Gong; Xiaopeng Fan; Yazhou Li; Bing Li; Nan Zhang; Raphael Gromig; Emma C. Smith; Wolf Dummann; Sophie Berger; Olaf Eisen; Jan Tell; Boris K. Biskaborn; et al. (Journal of Marine Science and Engineering, 2019)
Coring sediments in subglacial aquatic environments offers unique opportunities for research on paleo-environments and paleo-climates because it can provide data from periods even earlier than ice cores, as well as the overlying ice histories, interactions between ice and the water system, life forms in extreme habitats, sedimentology, and stratigraphy. However, retrieving sediment cores from a subglacial environment faces more difficulties than sediment coring in oceans and lakes, resulting in low yields from the most current subglacial sediment coring methods. The coring tools should pass through a hot water-drilled access borehole, then the water column, to reach the sediment layers. The access boreholes are size-limited by the hot water drilling tools and techniques. These holes are drilled through ice up to 3000–4000 m thick, with diameters ranging from 10–60 cm, and with a refreezing closure rate of up to 6 mm/h after being drilled. Several purpose-built streamline corers have been developed to pass through access boreholes and collect the sediment core. The main coring objectives are as follows: (i) To obtain undisturbed water–sediment cores, either singly or as multi-cores and (ii) to obtain long cores with minimal stratigraphic deformation. Subglacial sediment coring methods use similar tools to those used in lake and ocean coring. These methods include the following: Gravity coring, push coring, piston coring, hammer or percussion coring, vibrocoring, and composite methods. Several core length records have been attained by different coring methods, including a 290 cm percussion core from the sub-ice-shelf seafloor, a 400 cm piston core from the sub-ice-stream, and a 170 cm gravity core from a subglacial lake. There are also several undisturbed water–sediment cores that have been obtained by gravity corers or hammer corers. Most current coring tools are deployed by winch and cable facilities on the ice surface. There are three main limitations for obtaining long sediment cores which determines coring tool development, as follows: Hot-water borehole radial size restriction, the sedimentary structure, and the coring techniques. In this paper, we provide a general view on current developments in coring tools, including the working principles, corer characteristics, operational methods, coring site locations, field conditions, coring results, and possible technical improvements. Future prospects in corer design and development are also discussed.

Excitation energy transfer in the far-red absorbing violaxanthin/vaucheriaxanthin chlorophyll a complex from the eustigmatophyte alga FP5 - Dariusz M. Niedzwiedzki; Benjamin M. Wolf; Robert E. Blankenship (Photosynthesis Research, 2019)

Constraining N cycling in the ecosystem model LandscapeDNDC with the stable isotope model SIMONE - Tobias R. A. Denk; David Kraus; Ralf Kiese; Klaus Butterbach‐Bahl; Benjamin Wolf (Ecology, 2019)
The isotopic composition (ic) of soil nitrogen (N) and, more recently, the intramolecular distribution of 15 N in the N 2 O molecule (site preference, SP) are powerful instruments to identify dominant N turnover processes, and to attribute N 2 O emissions to their source processes. Despite the process information contained in the ic of N species and the associated potential for model validation, the implementation of isotopes in ecosystem models has lagged behind. To foster the validation of ecosystem models based on the ic of N species, we developed the stable isotope model for nutrient cycles (SIMONE). SIMONE uses fluxes between ecosystem N pools (soil organic N, mineral N, plants, microbes) calculated by biogeochemical models, and literature isotope effects for these processes to calculate the ic of N species. Here, we present the concept of SIMONE, apply it to simulations of the biogeochemical model LandscapeDNDC, and assess the capability of 15 N‐N 2 O and, to our knowledge for the first time, SP, to constrain simulated N fluxes by LandscapeDNDC. LandscapeDNDC successfully simulated N 2 O emission, soil nitrate, and ammonium, as well as soil environmental conditions of an intensively managed grassland site in Switzerland. Accordingly, the dynamics of 15 N‐N 2 O and SP of soil N 2 O fluxes as simulated by SIMONE agreed well with measurements, though 15 N‐N 2 O was on average underestimated and SP overestimated (root‐mean‐square error [RMSE] of 8.4‰ and 7.3‰, respectively). Although 15 N‐N 2 O could not constrain the N cycling process descriptions of LandscapeDNDC, the overestimation of SP indicated an overestimation of simulated nitrification rates by 10–59% at low water content, suggesting the revision of the corresponding model parameterization. Our findings show that N isotope modeling in combination with only recently available high‐ frequency measurements of the N 2 O ic are promising tools to identify and address weaknesses in N cycling of ecosystem models. This will finally contribute to augmenting the development of model‐based strategies for mitigating N pollution.

Global wheat production with 1.5 and 2.0°C above pre‐industrial warming - Bing Liu; Pierre Martre; Frank Ewert; John R. Porter; Andy J. Challinor; Christoph Müller; Alex C. Ruane; Katharina Waha; Peter J. Thorburn; Pramod K. Aggarwal; Mukhtar Ahmed; Juraj Balkovič; et al. (Global Change Biology, 2019)
Efforts to limit global warming to below 2°C in relation to the pre‐industrial level are under way, in accordance with the 2015 Paris Agreement. However, most impact research on agriculture to date has focused on impacts of warming >2°C on mean crop yields, and many previous studies did not focus sufficiently on extreme events and yield interannual variability. Here, with the latest climate scenarios from the Half a degree Additional warming, Prognosis and Projected Impacts (HAPPI) project, we evaluated the impacts of the 2015 Paris Agreement range of global warming (1.5 and 2.0°C warming above the pre‐industrial period) on global wheat production and local yield variability. A multi‐crop and multi‐climate model ensemble over a global network of sites developed by the Agricultural Model Intercomparison and Improvement Project (AgMIP) for Wheat was used to represent major rainfed and irrigated wheat cropping systems. Results show that projected global wheat production will change by −2.3% to 7.0% under the 1.5°C scenario and −2.4% to 10.5% under the 2.0°C scenario, compared to a baseline of 1980–2010, when considering changes in local temperature, rainfall, and global atmospheric CO 2 concentration, but no changes in management or wheat cultivars. The projected impact on wheat production varies spatially; a larger increase is projected for temperate high rainfall regions than for moderate hot low rainfall and irrigated regions. Grain yields in warmer regions are more likely to be reduced than in cooler regions. Despite mostly positive impacts on global average grain yields, the frequency of extremely low yields (bottom 5 percentile of baseline distribution) and yield inter‐annual variability will increase under both warming scenarios for some of the hot growing locations, including locations from the second largest global wheat producer—India, which supplies more than 14% of global wheat. The projected global impact of warming

Climate change impact and adaptation for wheat protein - Senthold Asseng; Pierre Martre; Andrea Maiorano; Reimund P. Rötter; Garry J. O’Leary; Glenn J. Fitzgerald; Christine Girousse; Rosella Motzo; Francesco Giunta; M. Ali Babar; Matthew P. Reynolds; Ahmed M. S. Kheir; et al. (Global Change Biology, 2019)
Wheat grain protein concentration is an important determinant of wheat quality for human nutrition that is often overlooked in efforts to improve crop production. We tested and applied a 32‐multi‐model ensemble to simulate global wheat yield and quality in a changing climate. Potential benefits of elevated atmospheric CO 2 concentration by 2050 on global wheat grain and protein yield are likely to be negated by impacts from rising temperature and changes in rainfall, but with considerable disparities between regions. Grain and protein yields are expected to be lower and more variable in most low‐rainfall regions, with nitrogen availability limiting growth stimulus from elevated CO 2 . Introducing genotypes adapted to warmer temperatures (and also considering changes in CO 2 and rainfall) could boost global wheat yield by 7% and protein yield by 2%, but grain protein concentration would be reduced by −1.1 percentage points, representing a relative change of −8.6%. Climate change adaptations that benefit grain yield are not always positive for grain quality, putting additional pressure on global wheat production.

Trade‐offs between soil carbon sequestration and reactive nitrogen losses under straw return in global agroecosystems - Longlong Xia; Shu Kee Lam; Benjamin Wolf; Ralf Kiese; Deli Chen; Klaus Butterbach‐Bahl (Global Change Biology, 2018)
It is widely recommended that crop straw be returned to croplands to maintain or increase soil carbon (C) storage in arable soils. However, because C and nitrogen (N) biogeochemical cycles are closely coupled, straw return may also affect soil reactive N (Nr) losses, but these effects remain uncertain, especially in terms of the interactions between soil C sequestration and Nr losses under straw addition. Here, we conducted a global meta‐analysis using 363 publications to assess the overall effects of straw return on soil Nr losses, C sequestration and crop productivity in agroecosystems. Our results show that on average, compared to mineral N fertilization, straw return with same amount of mineral N fertilizer significantly increased soil organic C (SOC) content (14.9%), crop yield (5.1%), and crop N uptake (10.9%). Moreover, Nr losses in the form of nitrous oxide (N 2 O) emissions from rice paddies (17.3%), N leaching (8.7%), and runoff (25.6%) were significantly reduced, mainly due to enhanced microbial N immobilization. However, N 2 O emissions from upland fields (21.5%) and ammonia (NH 3 ) emissions (17.0%) significantly increased following straw return, mainly due to the stimulation of nitrification/denitrification and soil urease activity. The increase in NH 3 and N 2 O emissions was significantly and negatively correlated with straw C/N ratio and soil clay content. Regarding the interactions between C sequestration and Nr losses, the increase in SOC content following straw return was significantly and positively correlated with the decrease in N leaching and runoff. However, at a global scale, straw return increased net Nr losses from both rice and upland fields due to a greater stimulation of NH 3 emissions than the reduction in N leaching and runoff. The trade‐offs between increased net Nr losses and soil C sequestration highlight the importance of reasonably managing straw return to soils to limit NH 3 emissions without decreasing associated C sequestration potential.

Multimodel ensembles improve predictions of crop–environment–management interactions - Daniel Wallach; Pierre Martre; Bing Liu; Senthold Asseng; Frank Ewert; Peter J. Thorburn; Martin van Ittersum; Pramod K. Aggarwal; Mukhtar Ahmed; Bruno Basso; Christian Biernath; Davide Cammarano; et al. (Global Change Biology, 2018)
A recent innovation in assessment of climate change impact on agricultural production has been to use crop multimodel ensembles ( MME s). These studies usually find large variability between individual models but that the ensemble mean (e‐mean) and median (e‐median) often seem to predict quite well. However, few studies have specifically been concerned with the predictive quality of those ensemble predictors. We ask what is the predictive quality of e‐mean and e‐median, and how does that depend on the ensemble characteristics. Our empirical results are based on five MME studies applied to wheat, using different data sets but the same 25 crop models. We show that the ensemble predictors have quite high skill and are better than most and sometimes all individual models for most groups of environments and most response variables. Mean squared error of e‐mean decreases monotonically with the size of the ensemble if models are added at random, but has a minimum at usually 2–6 models if best‐fit models are added first. Our theoretical results describe the ensemble using four parameters: average bias, model effect variance, environment effect variance, and interaction variance. We show analytically that mean squared error of prediction ( MSEP ) of e‐mean will always be smaller than MSEP averaged over models and will be less than MSEP of the best model if squared bias is less than the interaction variance. If models are added to the ensemble at random, MSEP of e‐mean will decrease as the inverse of ensemble size, with a minimum equal to squared bias plus interaction variance. This minimum value is not necessarily small, and so it is important to evaluate the predictive quality of e‐mean for each target population of environments. These results provide new information on the advantages of ensemble predictors, but also show their limitations.

3D Reconstruction of Scoliotic Spines from Stereoradiography and Depth Imaging - Benjamin Groisser; Ron Kimmel; Guy Feldman; Nimrod Rozen; Alon Wolf (Annals of Biomedical Engineering, 2018)

Characterization of a newly isolated freshwater Eustigmatophyte alga capable of utilizing far-red light as its sole light source - Benjamin M. Wolf; Dariusz M. Niedzwiedzki; Nikki Cecil M. Magdaong; Robyn Roth; Ursula Goodenough; Robert E. Blankenship (Photosynthesis Research, 2018)

Photoactivation and relaxation studies on the cyanobacterial orange carotenoid protein in the presence of copper ion - Haijun Liu; Yue Lu; Benjamin Wolf; Rafael Saer; Jeremy D. King; Robert E. Blankenship (Photosynthesis Research, 2018)

Subcellular pigment distribution is altered under far-red light acclimation in cyanobacteria that contain chlorophyll f - Erica L.-W. Majumder; Benjamin M. Wolf; Haijun Liu; R. Howard Berg; Jerilyn A. Timlin; Min Chen; Robert E. Blankenship (Photosynthesis Research, 2017)

Relating belowground microbial composition to the taxonomic, phylogenetic, and functional trait distributions of trees in a tropical forest - Albert Barberán; Krista L. McGuire; Jeffrey A. Wolf; F. Andrew Jones; Stuart Joseph Wright; Benjamin L. Turner; Adam Essene; Stephen P. Hubbell; Brant C. Faircloth; Noah Fierer (Ecology Letters, 2015)
The complexities of the relationships between plant and soil microbial communities remain unresolved. We determined the associations between plant aboveground and belowground (root) distributions and the communities of soil fungi and bacteria found across a diverse tropical forest plot. Soil microbial community composition was correlated with the taxonomic and phylogenetic structure of the aboveground plant assemblages even after controlling for differences in soil characteristics, but these relationships were stronger for fungi than for bacteria. In contrast to expectations, the species composition of roots in our soil core samples was a poor predictor of microbial community composition perhaps due to the patchy, ephemeral, and highly overlapping nature of fine root distributions. Our ability to predict soil microbial composition was not improved by incorporating information on plant functional traits suggesting that the most commonly measured plant traits are not particularly useful for predicting the plot‐level variability in belowground microbial communities.

Geospatial observations on tropical forest surface soil chemistry - Jeffrey A. Wolf; Stephen P. Hubbell; Geoffrey A. Fricker; Benjamin L. Turner (Ecology, 2015)
At plot scales ( 2 ) used to study tropical forest plant communities the causes of spatial heterogeneity of soils are disputed. We collected, georeferenced, and chemically analyzed a large spatial sample of soil cores ( n = 625 sites, 6.25 cm diameter × 10 cm depth cores) on an approximately 28 m regular grid from the Barro Colorado Island (BCI) 50‐ha (0.5 km 2 ) forest dynamics plot (FDP), Republic of Panama (9.15° N, 79.8° W). Here we present these data for general use. We also present differential GPS measurements of the plot corners for the BCI 50‐ha FDP, which aid in geospatial research in one of the most studied tropical forests. Further, we present a free open source command line software program written in Python that allows point data referenced to the plot coordinate system to be converted to a projected coordinate reference system for geospatial research. Together, the data sets allow for testing the drivers of soil heterogeneity in a tropical tree community using a wide variety of geospatial data sources.

CTFS ‐Forest GEO : a worldwide network monitoring forests in an era of global change - Kristina J. Anderson‐Teixeira; Stuart J. Davies; Amy C. Bennett; Erika B. Gonzalez‐Akre; Helene C. Muller‐Landau; S. Joseph Wright; Kamariah Abu Salim; Angélica M. Almeyda Zambrano; Alfonso Alonso; Jennifer L. Baltzer; Yves Basset; Norman A. Bourg; et al. (Global Change Biology, 2015)
Global change is impacting forests worldwide, threatening biodiversity and ecosystem services including climate regulation. Understanding how forests respond is critical to forest conservation and climate protection. This review describes an international network of 59 long‐term forest dynamics research sites ( CTFS ‐Forest GEO ) useful for characterizing forest responses to global change. Within very large plots (median size 25 ha), all stems ≥1 cm diameter are identified to species, mapped, and regularly recensused according to standardized protocols. CTFS ‐Forest GEO spans 25°S–61°N latitude, is generally representative of the range of bioclimatic, edaphic, and topographic conditions experienced by forests worldwide, and is the only forest monitoring network that applies a standardized protocol to each of the world's major forest biomes. Supplementary standardized measurements at subsets of the sites provide additional information on plants, animals, and ecosystem and environmental variables. CTFS ‐Forest GEO sites are experiencing multifaceted anthropogenic global change pressures including warming (average 0.61 °C), changes in precipitation (up to ±30% change), atmospheric deposition of nitrogen and sulfur compounds (up to 3.8 g N m −2 yr −1 and 3.1 g S m −2 yr −1 ), and forest fragmentation in the surrounding landscape (up to 88% reduced tree cover within 5 km). The broad suite of measurements made at CTFS ‐Forest GEO sites makes it possible to investigate the complex ways in which global change is impacting forest dynamics. Ongoing research across the CTFS ‐Forest GEO network is yielding insights into how and why the forests are changing, and continued monitoring will provide vital contributions to understanding worldwide forest diversity and dynamics in an era of global change.

The ENIGMA Consortium: large-scale collaborative analyses of neuroimaging and genetic data - Paul M. Thompson; Jason L. Stein; Sarah E. Medland; Derrek P. Hibar; Alejandro Arias Vasquez; Miguel E. Renteria; Roberto Toro; Neda Jahanshad; Gunter Schumann; Barbara Franke; Margaret J. Wright; Nicholas G. Martin; et al. (Brain Imaging and Behavior, 2014)

Grazing effects on the greenhouse gas balance of a temperate steppe ecosystem - Philipp Schönbach; Benjamin Wolf; Uta Dickhöfer; Martin Wiesmeier; Weiwei Chen; Hongwei Wan; Martin Gierus; Klaus Butterbach-Bahl; Ingrid Kögel-Knabner; Andreas Susenbeth; Xunhua Zheng; Friedhelm Taube (Nutrient Cycling in Agroecosystems, 2012)

Modeling N2O emissions from steppe in Inner Mongolia, China, with consideration of spring thaw and grazing intensity - Benjamin Wolf; Ralf Kiese; Weiwei Chen; Rüdiger Grote; Xunhua Zheng; Klaus Butterbach-Bahl (Plant and Soil, 2012)

Carbon sequestration potential of tropical pasture compared with afforestation in Panama - SEBASTIAN WOLF; WERNER EUGSTER; CATHERINE POTVIN; BENJAMIN L. TURNER; NINA BUCHMANN (Global Change Biology, 2011)
Tropical forest ecosystems play an important role in regulating the global climate, yet deforestation and land‐use change mean that the tropical carbon sink is increasingly influenced by agroecosystems and pastures. Despite this, it is not yet fully understood how carbon cycling in the tropics responds to land‐use change, particularly for pasture and afforestation. Thus, the objectives of our study were: (1) to elucidate the environmental controls and the impact of management on gross primary production (GPP), total ecosystem respiration (TER) and net ecosystem CO 2 exchange (NEE); (2) to estimate the carbon sequestration potential of tropical pasture compared with afforestation; and (3) to compare eddy covariance‐derived carbon budgets with biomass and soil inventory data. We performed comparative measurements of NEE in a tropical C 4 pasture and an adjacent afforestation with native tree species in Sardinilla (Panama) from 2007 to 2009. Pronounced seasonal variation in GPP, TER and NEE were closely related to radiation, soil moisture, and C 3 vs. C 4 plant physiology. The shallow rooting depth of grasses compared with trees resulted in a higher sensitivity of the pasture ecosystem to water limitation and seasonal drought. During 2008, substantial amounts of carbon were sequestered by the afforestation (–442 g C m –2 , negative values denote ecosystem carbon uptake), which was in agreement with biometric observations (–450 g C m –2 ). In contrast, the pasture ecosystem was a strong carbon source in 2008 and 2009 (261 g C m –2 ), associated with seasonal drought and overgrazing. In addition, soil carbon isotope data indicated rapid carbon turnover after conversion from C 4 pasture to C 3 afforestation. Our results clearly show the potential for considerable carbon sequestration of tropical afforestation and highlight the risk of carbon losses from pasture ecosystems in a seasonal tropical climate.

Annual methane uptake by temperate semiarid steppes as regulated by stocking rates, aboveground plant biomass and topsoil air permeability - WEIWEI CHEN; BENJAMIN WOLF; XUNHUA ZHENG; ZHISHENG YAO; KLAUS BUTTERBACH‐BAHL; NICOLAS BRÜGGEMANN; CHUNYAN LIU; SHENGHUI HAN; XINGGUO HAN (Global Change Biology, 2011)
Overgrazing‐induced degradation of temperate semiarid steppes may affect the soil sink for atmospheric methane (CH 4 ). However, previous studies have primarily focused on the growing season and on single grazing patterns. Thus, the response of annual CH 4 uptake by steppes compared with various grazing practices is uncertain. In this study, we investigated the effects of grazing on the annual CH 4 uptake by two typical Eurasian semiarid steppes (the Stipa grandis steppe and the Leymus chinensis steppe) located in Inner Mongolia, China. The CH 4 fluxes were measured year‐round using static chambers and gas chromatography at 12 field sites that differed primarily in grazing intensities. Our results indicated that steppe soils were CH 4 sinks throughout the year. The annual CH 4 uptake correlated with stocking rates, whereas the seasonality of CH 4 uptake was primarily dominated by temperature. The annual CH 4 uptake at all sites averaged 3.7±0.7 kg C ha −1 yr −1 (range: 2.3–4.5), where approximately 35% (range: 23–40%) occurred during the nongrowing season. Light‐to‐moderate grazing (stocking rate≤1 sheep ha −1 yr −1 ) did not significantly change the annual CH 4 uptake compared with ungrazed steppes, but heavy grazing reduced annual CH 4 uptake significantly (by 24–31%, P 4 . The empirical equations based on the significant relationships between annual CH 4 uptake and stocking rates, aboveground plant biomass and topsoil air permeability ( P 4 uptake by temperate semiarid steppes.

Feedback of grazing on gross rates of N mineralization and inorganic N partitioning in steppe soils of Inner Mongolia - Honghui Wu; Michael Dannenmann; Nicole Fanselow; Benjamin Wolf; Zhisheng Yao; Xing Wu; Nicolas Brüggemann; Xunhua Zheng; Xingguo Han; Klaus Dittert; Klaus Butterbach-Bahl (Plant and Soil, 2011)

Annual emissions of greenhouse gases from sheepfolds in Inner Mongolia - Weiwei Chen; Benjamin Wolf; Nicolas Brüggemann; Klaus Butterbach-Bahl; Xunhua Zheng (Plant and Soil, 2011)

Yellow crazy ant (Anoplolepis gracilipes) invasions within undisturbed mainland Australian habitats: no support for biotic resistance hypothesis - Benjamin D. Hoffmann; Wolf-Christian Saul (Biological Invasions, 2010)

Spatial variability of N2O, CH4 and CO2 fluxes within the Xilin River catchment of Inner Mongolia, China: a soil core study - Zhisheng Yao; Benjamin Wolf; Weiwei Chen; Klaus Butterbach-Bahl; Nicolas Brüggemann; Martin Wiesmeier; Michael Dannenmann; Benjamin Blank; Xunhua Zheng (Plant and Soil, 2010)